2018
DOI: 10.3390/cancers10060185
|View full text |Cite
|
Sign up to set email alerts
|

Cutting to the Chase: How Matrix Metalloproteinase-2 Activity Controls Breast-Cancer-to-Bone Metastasis

Abstract: Bone metastatic breast cancer is currently incurable and will be evident in more than 70% of patients that succumb to the disease. Understanding the factors that contribute to the progression and metastasis of breast cancer can reveal therapeutic opportunities. Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes whose role in cancer has been widely documented. They are capable of contributing to every step of the metastatic cascade, but enthusiasm for the use of MMP inhibition as a therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 111 publications
0
39
0
Order By: Relevance
“…Although not all the key players in the development of bone metastases are yet known, multiple molecules and signaling pathways appear to be important for metastasis. Indeed, in addition to the IGF pathway, NF-kB, matrix metalloproteases, and the Wnt, stromal cell-derived factor 1 (CXCL12)/C-X-C chemokine receptor type 4 (CXCR4) and PI3K/AKT signaling axes may also play key roles in the development and progression of bone metastases (39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Biology Of Bone Metastasesmentioning
confidence: 99%
“…Although not all the key players in the development of bone metastases are yet known, multiple molecules and signaling pathways appear to be important for metastasis. Indeed, in addition to the IGF pathway, NF-kB, matrix metalloproteases, and the Wnt, stromal cell-derived factor 1 (CXCL12)/C-X-C chemokine receptor type 4 (CXCR4) and PI3K/AKT signaling axes may also play key roles in the development and progression of bone metastases (39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Biology Of Bone Metastasesmentioning
confidence: 99%
“…[4] Since their discovery,M MPs have emerged as an intriguing target in pharmaceuticalr esearch. [5][6][7][8][9] Due to the involvement of members of the MMP family in am ultitude of severe diseases, such as cancer, [10][11][12][13][14][15][16] arthritis, [17,18] chronic obstructive pulmonary disease (COPD), [19][20][21] or sepsis, [22][23][24][25] great efforts weret aken to modulate MMP activity to possibly treat diseases in which MMP activity is out of balance. [26,27] Due to side effects evolving from al ack of selectivity and insufficient knowledge aboutt he relevance of the target family in pathological processes, no compound designed as an MMP inhibitor has reached the market so far,a nd clinicalt rials have failed.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue inhibitors of metalloproteinases (TIMPs) are endogenous proteins which could prohibit cell proliferation and migration by inhibiting the function of Matrix metalloproteinases (MMPs). Previous studies have shown that when the balance between TIMPs and MMPs was disrupted, it could lead to the degradation of the extracellular matrix and induce tumor cell invasion, migration or other receptor-mediated changes [5]. Tissue inhibitor of metalloproteinase-2 (TIMP-2) is a unique inhibitor among the TIMP family members, because it not only correlates with matrix remodeling and angiogenesis suppressing but also involves in the process of tumor growth, inflammation, and other diseases [6].…”
Section: Introductionmentioning
confidence: 99%